Time of the low-level cardiopulmonary exercise test does not affect the evaluation of acute myocardial infarction in stable status - Zhao, Lanting; Liu, Yuanwei; Li, Siyuan; Xie, Ying; Xue, Yajun; Yuan, Yifang; He, Rong; She, Fei; Lv, Tingting; Zhang, Ping (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Cardiopulmonary exercise test (CPET) provides the means to evaluate the cardiopulmonary function and guide cardiac rehabilitation. The performance of acute myocardial infarction (AMI) patients at different times is different on CPET. Materials and methods: This was a cross-sectional study. Patients diagnosed as AMI in stable status were included and performed the low- level CPET (RAMP 10W). CPET variables at different times were compared among four groups. Results: Sixty and one patients with AMI conducted the low-level CPET from 3 to 15 days after AMI. Patients were stratified according to quartiles of CPET’s time: 5 in 3-6 days group, 34 in 7-9 days group, 14 in 10-12 days group, 8 in 13-15 days group. Only VO2/HR at rest showed statistically different among the four groups.VO2/HR at rest in 3-6 days group and 10-12 days group were higher than in 13-15 days group (3.4 ± 0.85, 3.18 ± 0.78 vs 2.50 ± 0.49 ml/beat, p < 0.05). Patients with complete revascularization had higher peak heart rate and blood pressure product and peak breathing reserve (BR), and lower Borg score compared with incomplete revascularization. And patients with LVEF >50% had higher peak BR compared with LVEF 40%-50%. Conclusion: It was safe and efficient to conduct the low-level CPET in stable AMI patients 3 days after onset. Time was not an effector on cardiopulmonary function and exercise capacity and prognosis in AMI during CPET. Complete revascularization and normal LVEF should be good for exercise test in AMI.